ANTIOXIDANT ACTIVITY AND FT-IR ANALYSIS OF DATURA INNOXIA AND DATURA METEL LEAF AND SEED METHANOLIC EXTRACTS - Bhardwaj, Khushboo; Kumar, Sanjiv; Ojha, Sudarshan (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Datura (family- Solanaceae), has a long history of being used as herbal medicine. These medicinal effects have beenattributed to the phytochemicals present in the plant leaves and seeds, in particular alkaloids, flavonoids and phenolic compounds.The objective of this study was to investigate the methanolic leaf and seed extracts of Datura innoxia (DLP-I & DSP-I) and Daturametel (DLP-M & DSP-M) for their total phenolic, flavonoids and in-vitro antioxidant properties.Materials and Methods: Determination of total phenolic content and total flavonoid content and antioxidant activity in terms oftotal antioxidant assay, ABTS assay, DPPH assay and in-vitro lipid peroxidation inhibiting activity were determined along with theFT-IR (Fourier transform infrared spectroscopy) analysis of the extracts.Results: The highest total phenolic and total flavonoid content were registered by the D. innoxia leaf extract (70.26 ± 1.12 mgGAE/g and 34.24 ± 1.28 mg RE/g respectively). Maximum DPPH radical scavenging activity was exerted by the leaf extract of D.innoxia (IC50 = 146.69 ± 8.46 μg/mL) among the four different methanolic extracts. The highest activity of the ABTS assay wasfound in Datura innoxia leaf extract (IC50 value = 149.42 ± 13.43 μg/mL) and the highest total antioxidant capacity was found to bepresent in D. innoxia leaf extract (221.25 ± 1.06 mg AAE/g) whereas D. metel seed extract registered the maximum lipidperoxidation inhibition activity (IC50 = 112 ± 1.30 μg/mL). The FT-IR data also supported the maximum activity in D. innoxia (leafand seed) extracts.Conclusion: The results thus obtained suggested that the plant Datura innoxia possess considerable antioxidant activity over Daturametel and therefore can be established as a potential source of natural antioxidant.